2004
DOI: 10.1177/154405910408300709
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Sarcoplasmic Reticulum Ca2+-dependent ATPase from Masticatory Muscles

Abstract: We compared the sarcoplasmic reticulum (SR) Ca-ATPase from masseter (M) and medial pterygoid (MP) muscles with that from fast muscles (FM) to examine whether its calcium transport capability and enzymatic activity are different. SR vesicles from FM, M, and MP muscles were obtained according to Champeil et al.(1985). Assays for characterization of the enzyme properties were performed. The results showed similar optimal conditions for the Ca-ATPase activity and calcium transport in M, MP, and FM. However, the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
2
4
0
Order By: Relevance
“…Our first experiments were devised to isolate highly pure SERCA from elevator and depressor masticatory muscles. As in earlier studies we demonstrated that the procedure of Champeil et al . allows the isolation of sealed SR membranes with highly specific Ca‐ATPase activity from both masticatory and fast‐twitch muscles, and this procedure was used to obtain SR membrane fragments.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Our first experiments were devised to isolate highly pure SERCA from elevator and depressor masticatory muscles. As in earlier studies we demonstrated that the procedure of Champeil et al . allows the isolation of sealed SR membranes with highly specific Ca‐ATPase activity from both masticatory and fast‐twitch muscles, and this procedure was used to obtain SR membrane fragments.…”
Section: Resultssupporting
confidence: 87%
“…Despite the above‐mentioned similarities, it seems likely that functional differences exist among the SERCA isoforms which, combined with masticatory muscle‐specific expression of fast‐ and slow‐twitch muscle isoforms, might result in lower Ca‐ATPase activity and calcium transport capability. This was recently reported for masseter and medial pterygoid muscles , and accounts for the heterogeneous composition of masticatory muscles. To test this hypothesis we used SERCA‐specific antibodies to assess the distribution of the different isoforms.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…Few authors have studied the Ca-ATPase from masticatory muscles (Okabe et al, 1985;Sánchez et al, 2004). Studies on the effect of dental drugs on the Ca-ATPase from masseter and medial pterygoid muscles have not yet been published.…”
Section: Introductionmentioning
confidence: 99%